A novel utilization of Bayer red mud through co-reduction with a limonitic laterite ore to prepare ferronickel. (10th April 2019) - Wang, Xiaoping; Sun, Tichang; Wu, Shichao; Chen, Chao; Kou, Jue; Xu, Chengyan
Abstract: The large-scale utilization problem of red mud remains a challenge. During the reduction of laterite ores to prepare ferronickel product, sodium or calcium salt usually needs to be added, but it would increase the raw material cost. Thus, the feasibility of co-reduction followed by magnetic separation of strong alkaline waste red mud and a limonitic laterite ore to prepare ferronickel was investigated. A ferronickel product containing 1.71 wt% nickel and 86.00 wt% iron was obtained, under the optimized co-reduction conditions of the red mud dosage of 20 wt%, the anthracite dosage of 16 wt%, the co-reduction duration of 70 min. The corresponding nickel and the total iron recoveries were 96.37 wt% and 97.72 wt%, respectively. Results showed that the co-reduction and comprehensive recovery of the iron ore in the red mud were achieved.